A matemática e jogos pedagógicos: ensino das quatro operações básicas: 5º ano do ensino fundamental - Silva, Marcelo Passinho da (2024)
This dissertation, entitled "Mathematics and educational games: teaching the four basic operations in the fifth year of Elementary School", is a work linked to the Postgraduate Program in Science and Mathematics Teaching at the University of Passo Fundo/RS (PPGCEM/UPF/RS), in the research line Educational practices in Science and Mathematics teaching, and was developed with a group of teachers from the city of Curuçá/PA. The aforementioned dissertation also generated an Educational Product (EP) entitled "Booklet for developing games involving the four basic mathematical operations". Both works will be available for free access on the PPGECM website: http:www.upf.br/ppgecm and on the EduCapes portal at the link: http://educapes.capes.gov.br/handle/capes/870227. The general objective of the work developed was to evaluate how, through the construction and use of educational games, together with 5th grade elementary school teachers, it can help in the teaching of the four basic operations of Mathematics. The dissertation developed had theoretical support in ideas of Lev Vygotsky, Jean Piaget and Kishimoto when these were linked to the central activity of the work, which was the creation and use of educational games. The application took place in the form of workshops with teachers who work with Mathematics, after an awareness-raising activity on the subject in some schools in the city of Curuçá/PA. The research developed was of a qualitative-analytical nature and had as data collection instruments a logbook and report of the activities developed. The results presented were satisfactory because the teachers, in addition to understanding the process of building the games, for later dissemination to other teachers and students, showed that they are resources with the potential to help them in teaching the four basic operations of Mathematics and at the same time have great value for the students, to promote in them a consistent learning about the subject or even to assist, in students with gaps in these operations, the possibility of appropriating the mathematical operational processes in a different way to what is commonly worked in schools.